2018
DOI: 10.2188/jea.je20170100
|View full text |Cite
|
Sign up to set email alerts
|

Parental Internet Use and Lifestyle Factors as Correlates of Prolonged Screen Time of Children in Japan: Results From the Super Shokuiku School Project

Abstract: BackgroundProlonged screen time (ST), which includes TV viewing and gaming on smartphones and computers, is linked to poor health. Our aim was to explore the associations between school children with prolonged ST and parental internet use (IU) and lifestyles in Japan.MethodsChildren aged 6 to 13 years from the Super Shokuiku School Project, were surveyed using questionnaires in 2016. The survey assessed the grade, sex, and lifestyle of 1,659 children and parental internet use (IU) and lifestyle using Breslow’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 28 publications
6
48
1
Order By: Relevance
“…Consistent with previous research [10,18,28,[64][65][66][67][68][69][70], mothers participating in the current study used several parenting practices such as monitoring time and content, setting limits and having rules, and prompting child to do something else to manage their preschool children's ST. Previous research suggests that parental monitoring, especially maternal monitoring, of ST is associated with less ST for children [56,62].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Consistent with previous research [10,18,28,[64][65][66][67][68][69][70], mothers participating in the current study used several parenting practices such as monitoring time and content, setting limits and having rules, and prompting child to do something else to manage their preschool children's ST. Previous research suggests that parental monitoring, especially maternal monitoring, of ST is associated with less ST for children [56,62].…”
Section: Discussionmentioning
confidence: 84%
“…This is important as research shows that children have increased ST when parents have ST themselves [50,[61][62][63][64]. A qualitative study conducted in the U.K. found that children whose parents engaged in ST with them had more ST than children whose parents prioritized and engaged with them in non-SV behaviors for relaxation and family time [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has a higher number of dual‐income households (53.9%) than the national average (45.4%), leading to household incomes that are higher (55 686 US $) than the national average (50 163 US $) . The results of this project have been published in other studies …”
Section: Methodsmentioning
confidence: 81%
“…Our study suggests that less than an hour for all media, not only television is recommended. A long time spent viewing or using media delays the time at which the child goes to bed . The excitement generated by viewing media before going to bed may cause a predominant state of the sympathetic activity and reduce the production of saliva, which induces dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation